2020
DOI: 10.3390/microorganisms8030439
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei A13 and High-Pressure Homogenization Stress Response

Abstract: Sub-lethal high-pressure homogenization treatments applied to Lactobacillus paracasei A13 demonstrated to be a useful strategy to enhance technological and functional properties without detrimental effects on the viability of this strain. Modification of membrane fatty acid composition is reported to be the main regulatory mechanisms adopted by probiotic lactobacilli to counteract high-pressure stress. This work is aimed to clarify and understand the relationship between the modification of membrane fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 73 publications
1
19
0
1
Order By: Relevance
“…For sure, their increase is a response to stress conditions. In fact, during the passage through the homogenizing valve, millisecond increases of temperature and a rise in gas partition into cytoplasmic membranes generated a marked oxidative stress for the cells that can be counteracted more or less effectively, depending on the microbial species, strains, and protocols applied (Siroli et al, 2020). Although, this is particularly true when cells are subjected to 150 and 200 MPa, it becomes minimal when a reduced pressure is applied, as in our case (50 MPa).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For sure, their increase is a response to stress conditions. In fact, during the passage through the homogenizing valve, millisecond increases of temperature and a rise in gas partition into cytoplasmic membranes generated a marked oxidative stress for the cells that can be counteracted more or less effectively, depending on the microbial species, strains, and protocols applied (Siroli et al, 2020). Although, this is particularly true when cells are subjected to 150 and 200 MPa, it becomes minimal when a reduced pressure is applied, as in our case (50 MPa).…”
Section: Discussionmentioning
confidence: 71%
“…Although literature data are consistent in reporting the positive effects of sub-lethal HPH treatments on the probiotic features (i.e., hydrophobicity and autoaggregation) in a strain dependent way, little is known about the microbial gene expression upon this stress. Recently, Siroli et al (2020) showed that L. paracasei A13 activated a series of reactions which aimed to control and stabilize membrane fluidity in response to HPH treatments inducing an upregulation of genes involved in fatty acids biosynthesis as an immediate response mechanism adopted by L. paracasei A13 to HPH. However, information is scarce following the application of HPH sublethal treatment on several stress response proteins, such as the chaperonins GroEL and DnaK, proteases ClpP, GroEL, and DnaK, which play a key role in several stress conditions (Frees et al, 2007;Weiss and Jespersen, 2010) and the genes involved in microbial cell adhesion in L. acidophilus.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the unsaturation in membrane fatty acids. [83] (-) indicates that the component has not been included in a food matrix Siroli et al [83] reported that the main regulatory mechanism that probiotic lactobacilli adopt to counteract pressure stress is the modification of the composition of membrane fatty acids. Specifically, they observed an increase in unsaturated fatty acids when HPH at 100 and 150 MPa was applied to Lactobacillus paracasei A13.…”
Section: Increase Of Bioavailability and Encapsulation Of Bioactive Compoundsmentioning
confidence: 99%
“…HPH treatments at pressure levels below 100 MPa, considered as sublethal pressures, are applied to microbial cultures: initiators, co-initiators, or probiotics and yeasts, in order to produce cultures with improved functional, technological and sensory properties. The use of strains belonging to the genus Bifidobacterium and Lactobacillus predominate as probiotics, and to a lesser extent Enterococcus, Streptococcus and Saccharomyces [78]. The bacterial cells response to mechanical stress induced by HPH modifying their metabolic activity and membrane composition.…”
Section: Increase Of Bioavailability and Encapsulation Of Bioactive Cmentioning
confidence: 99%
“…Siroli et al [84] reported that the main regulatory mechanism that probiotic lactobacilli adopt to counteract pressure stress is the modification of the composition of membrane fatty acids. Specifically, they observed an increase of unsaturated fatty acids when HPH at 100 and 150 MPa was applied to Lactobacillus paracasei A13.…”
Section: Increase Of Bioavailability and Encapsulation Of Bioactive Cmentioning
confidence: 99%